2018
DOI: 10.1044/2017_aja-16-0071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilateral Hearing Aid Use on Balance in Experienced Adult Hearing Aid Users

Abstract: These results failed to support previous research, which indicated that amplification of auditory input could benefit balance in individuals with hearing and balance disorders. Further research utilizing randomized controlled trials is needed to resolve the disparity between the current results and those of previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 10 publications
1
42
1
2
Order By: Relevance
“…McDaniel [ 12 ] used a dynamic posturography platform (SOT) to compare aided vs. unaided hearing in 22 experienced HA users (a vage 68 yrs) and found no difference in SOT performance. They concluded that randomized, controlled trials (RCT) should be undertaken to get more insights.…”
Section: Resultsmentioning
confidence: 99%
“…McDaniel [ 12 ] used a dynamic posturography platform (SOT) to compare aided vs. unaided hearing in 22 experienced HA users (a vage 68 yrs) and found no difference in SOT performance. They concluded that randomized, controlled trials (RCT) should be undertaken to get more insights.…”
Section: Resultsmentioning
confidence: 99%
“…The 8 studies included 4 cross-sectional studies [Lacerda et al, 2012;Rumalla et al, 2015;Shayman et al, 2017;McDaniel et al, 2018], 3 cross-sectional controlled studies [Vitkovic et al, 2016;Negahban et al, 2017;Maheu et al, 2019], and 1 prospective nonrandomized study [Weaver et al, 2017]. The characteristics of included studies are demonstrated in Table 1.…”
Section: Results Of Search Strategy and Description Of Studiesmentioning
confidence: 99%
“…Computerized posturography was used as objective measurement of static balance in 4 studies [Vitkovic et al, 2016;Negahban et al, 2017;McDaniel et al, 2018;Maheu et al, 2019], but the results are inconsistent. Out of a total of 41 patients with moderate hearing loss, McDaniel et al [2018] and Vitkovic et al [2016] did not find any significant difference on static balance between the aided and unaided performances (p = 0.124 and p > 0.05, respectively). Nevertheless, Vitkovic et al [2016] observed an improvement of static balance during the aided condition in presence of sound, compared to the trial without sound exposure (significant interaction between HAs trial and sound environment, p = 0.048).…”
Section: Objective Measurement Of Balance Static Balancementioning
confidence: 99%
“…The relationship between hearing aid use and injury prevention requires further study using welldefined and detailed measures of both hearing and hearing aid use, as prior work on this association has demonstrated mixed effects. 18,19 Understanding the association between hearing and falls is important for the inclusion of hearing loss and management in future falls prevention programs or analysis as hearing loss is commonly not included in prevention strategies 20 despite potentially being a prominent risk factor. Moreover, understanding how hearing aid use may modify the effectiveness of fall prevention programs has implications as a potential prevention strategy for reducing falls and improving health outcomes by geriatricians and primary care providers.…”
Section: Discussionmentioning
confidence: 99%